KONSEP ETIKA GURU DAN MURID DALAM ISLAM MENURUT AL-GHAZALI DALAM KITAB IHYA ULUMUDDIN - Faizah, Nurul; Zuhdi, Ahmad; Nugroho, Muhammad Yusuf Amin (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
The decline in the quality of education and the moral crisis in the world of eeducation, especially teachers and students, are increasingly rampant. One of the main causes is the fading of ethics, namely a collection of values and norms that should be a guide for teachers and students. Therefore, this study tries to explain and analyze the ethics of teachers and students that have been formulated by Al- Ghazali in his book Ihya Ulumuddin, which was later developed in an effort to restore the main character in the educational process, namely teachers and students who are ethical. This study uses a descriptive approach. Qualitative, the type of research is library research. The data collection technique in this research is to find data about variables in the form of books, journals, and so on. Analysis of the data used is content analysis. The conclusions resulting from this study, among others, according to Al-Ghazali in the book Ihya Ulumuddin a teachernmust have compassion for students, carry out their duties by always imitating the prophet, and intend only to get the pleasure of Allah swt. while a student according to Al-Ghazali must purify his soul from all despicable morals and always hope for the pleasure of Allah swt.